2022
DOI: 10.3390/molecules27020410
|View full text |Cite
|
Sign up to set email alerts
|

Umbu Fruit Peel as Source of Antioxidant, Antimicrobial and α-Amylase Inhibitor Compounds

Abstract: Herein, the extraction of bioactive compounds from umbu fruit peel was optimized using thermal-assisted solid–liquid extraction. In parallel, antioxidant, antimicrobial, and inhibitory effects against α-amylase of optimized extract were also evaluated. The combination of operational conditions including the temperature (32–74 °C), ethanol concentration (13–97%), and solid/liquid ratio (1:10–1:60; w/v) was employed using a rotational central composite design for optimization. The extracts were evaluated for tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Purple-fleshed pitanga had the highest scavenging activity in the 2,2-diphenyl-2-picrylhydrazyl hydrate (DPPH) assay, with IC 50 of 37 mg/L, and also showed the highest FRAP, followed by xavante blackberries, Cherokee blackberries, and araçá. Moreover, bioactive compounds from peel of a Brazilian native fruit, umbu fruit (Spondias tuberosa), showed total phenolic compounds (1985 mg gallic acid equivalent/100 g), total flavonoid compounds (1364 mg rutin equivalent/100 g) and antioxidant capacity by ABTS (122 µmol Trolox equivalent/g), DPPH (174 µmol/Trolox equivalent g) and FRAP assays (468 µmol Fe 2+ /g) [148]. It can be concluded that fruits rich in phenolic compounds have high antioxidant activity.…”
Section: Antioxidant Properties Of Fruit Extractsmentioning
confidence: 99%
“…Purple-fleshed pitanga had the highest scavenging activity in the 2,2-diphenyl-2-picrylhydrazyl hydrate (DPPH) assay, with IC 50 of 37 mg/L, and also showed the highest FRAP, followed by xavante blackberries, Cherokee blackberries, and araçá. Moreover, bioactive compounds from peel of a Brazilian native fruit, umbu fruit (Spondias tuberosa), showed total phenolic compounds (1985 mg gallic acid equivalent/100 g), total flavonoid compounds (1364 mg rutin equivalent/100 g) and antioxidant capacity by ABTS (122 µmol Trolox equivalent/g), DPPH (174 µmol/Trolox equivalent g) and FRAP assays (468 µmol Fe 2+ /g) [148]. It can be concluded that fruits rich in phenolic compounds have high antioxidant activity.…”
Section: Antioxidant Properties Of Fruit Extractsmentioning
confidence: 99%
“…Its linear effect was significant and positive. In this way, higher temperatures favor the solubility of phenolic compounds and decrease the viscosity of the extraction system, leading to a better extraction yield [ 16 , 30 ]. Notably, this behavior was also observed for the antioxidant capacity of the extracts regardless of the method used ( Table 1 , Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature was limited to 74 °C to avoid loss of solvent. The extraction of antioxidant compounds was performed by agitated solvent extraction, using 125 mL glass flasks properly covered and heated for 1 h under constant stirring of 150 rpm, conditions based on preliminary studies and literature data [ 15 , 16 ]. The experimental data were analyzed by response surface methodology using a second order polynomial equation.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several studies have documented health benefits associated with the fruit and their components. Antioxidant and antibacterial actions, acetylcholinesterase inhibition, and cancer chemopreventive activity have already been reported [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 95%
“…In the same study, the authors identified the presence of gallotannins and ellagitannins as the main tannins present in this plant species. Ribeiro et al [23] reported fifteen compounds in the optimized extract of S. tuberosa peel, which mainly comprised phenolic acids and flavonoids.…”
Section: Spondias Tuberosamentioning
confidence: 99%